PENGARUH PEMANFAATAN MEDIA SOSIAL WHATSAPP TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI - Ni Wayan Ayunita Padmiyani; Gede Eka Puja Dyatmika; Ni Made Ria Taurisia Armayani (Padma Sari: Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the effect of the use of WhatsApp social media on the learning outcomes of Hindu religious education and character for class X students at SMK Negeri 4 Mataram in the 2020/2021 academic year. This study uses a quantitative approach and is an ex post facto research using correlational associative analysis. Ex post facto research is research that examines causal relationships that are not manipulated or treated (designed and implemented) by the researcher. Data were collected using questionnaires and documentation. The data analysis technique uses product moment correlation. The results of the study indicate that there is an effect of the use of WhatsApp social media on the learning outcomes of Hindu religious education and character for class X students at SMK Negeri 4 Mataram in the 2020/2021 academic year. The magnitude of the influence of the use of WhatsApp social media on the learning outcomes of Hindu religious education and the character of class X students (rxy) is 0.378, while the contribution of WhatsApp social media is 14.28%. This means that there is another factor of 85.72% of the learning outcomes of Hindu religious education and character for class X students at SMK Negeri 4 Mataram. The conclusion of this study is that there is an effect of the use of WhatsApp social media on the learning outcomes of Hindu religious education and character for class X students at SMK Negeri 4 Mataram in the 2020/2021 academic year, with the contribution of using WhatsApp social media by 14.28%. Base on the research result, applied social media WhatsApp can be use in other learning.